Suicidal Behaviors and Risk Taking Among Homeless Individuals: A Systematic Review and Meta-Analysis. - Armoon, Bahram; Griffiths, Mark D.; Mohammadi, Rasool; Ahounbar, Elaheh (Community Mental Health Journal, 2023)
The present systematic review and meta-analysis study aimed to determine sociodemographic characteristics, risky behaviors, mental health disorders, and substance use disorders associated with suicide behaviors including suicidal ideation and suicide attempts among homeless individuals. PubMed, Scopus, Web of Science, and Cochrane Library databases were searched to identify the relevant studies published between January 1, 1995 and November 1, 2022. After initial evaluation of 9,094 papers, a total of 23 studies met the eligibility criteria. Results of the present study showed that chronic physical illnesses, violent behaviors, mood and psychotic disorders, and substance use disorders were significantly associated with both suicidal ideation and suicide attempts, while being older, having a history of physical abuse, and having mood and post-traumatic stress disorders were associated with suicide attempts only. The present study's findings suggest a crucial need for facilitating access to mental healthcare plans and promoting mental healthcare seeking among homeless individuals.